2001
DOI: 10.1046/j.1365-2567.2001.01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and recycling of the complex between CD23 and HLA‐DR in human B cells

Abstract: SUMMARYThe presentation of extremely low doses of antigen to T cells is enhanced by immunoglobulin E (IgE)-dependent antigen focusing to CD23, the low-af®nity receptor for IgE, expressed on activated B cells. CD23 contains a C-type lectin domain in its extracellular sequence and a targeting signal for coated pits, required for endocytosis, in its cytoplasmic sequence. CD23 is non-covalently associated with the major histocompatibility complex class II antigen, human leucocyte antigen HLA-DR, on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 66 publications
6
50
0
Order By: Relevance
“…Especially when using EBV-transformed B cell lines, which should be free of contaminating cell types, contribution of DCs to the T cell stimulation/Ag presentation is excluded (26 -28). This, taken along with the fact that human B cells have been shown to internalize IgE/Ag via CD23 (57,58), strongly suggest that CD23 ϩ B cells can indeed present IgE-Ag complexes to specific T cells in vitro. Whether this also takes place in vivo is more difficult to ascertain.…”
Section: Discussionmentioning
confidence: 95%
“…Especially when using EBV-transformed B cell lines, which should be free of contaminating cell types, contribution of DCs to the T cell stimulation/Ag presentation is excluded (26 -28). This, taken along with the fact that human B cells have been shown to internalize IgE/Ag via CD23 (57,58), strongly suggest that CD23 ϩ B cells can indeed present IgE-Ag complexes to specific T cells in vitro. Whether this also takes place in vivo is more difficult to ascertain.…”
Section: Discussionmentioning
confidence: 95%
“…[25][26][27] The proposed roles for CD23 in antigen presentation include the binding of antigen-IgE-antibody complexes, internalization of the complexes, transport to compartments of the endosomal network containing proteolytic enzymes, interaction with major histocompatibility complex (MHC) class II antigens and interaction with CD21 at the points of contact on the Band T-cell surfaces. 28,29 An integrated CD23 is believed to be important for the IgE-mediated antigen presentation. A stabilized CD23 on the antigen presenting cells may result in enhanced T-cell proliferation in response to antigen.…”
Section: Discussionmentioning
confidence: 99%
“…43 As the binding of CD23 to MHC II has been observed to be involved in CD23-mediated antigen presentation, it is quite possible that loss of N-glycosylation may lead to functional changes in the binding affinity of CD23 to MHC II and result in enhanced IgEantigen complex presentation. 28 The genetic polymorphism R62W is expected to affect these various functions via the involvement of N-glycosylation. A further clarification of association of the genetic polymorphism R62W with IgE binding affinity and its interaction with MHCII will offer other potential mechanisms to understand the significance of R62W in specific immunological and allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…1A), indicating that BCRm + B cells have multiple Ig surface receptors, likely of many differing specificities. Previous studies have demonstrated that Ag captured via CD23-bound IgE is processed and presented on surface MHC class II within hours (15), suggesting that CD23 is highly efficient in inducing Ag presentation functions. These observations raise the question of how a B cell would "decide" which receptor (CD23 or BCR) or Ag, is the priority in generating a response.…”
Section: Cd23mentioning
confidence: 99%
“…However, the influence of CD23-bound IgE on human B cellmediated immunity is poorly described. Experimental evidence suggests that cross-linking CD23-bound IgE on B cells increases the recycling of HLA-DR complexes to the surface of the cell, suggesting a role in Ag presentation (15); however, there are conflicting reports as to whether surface CD23 is a negative or positive regulator of IgE in humans (9,16). We therefore sought to better define the effect of CD23-bound IgE on human B cell activation and present a potential role for CD23 + B cells in the development of resistance to schistosomiasis.…”
mentioning
confidence: 99%